Skeletal muscle metabolic characteristics and fresh meat quality defects associated with wooden breast - Rimmer, Linnea A.; Zumbaugh, Morgan D. (Frontiers in Physiology, 2024)
Wooden breast (WB) is a myopathy that occurs in pectoralis major (PM) muscles, predominately affecting large, fast-growing broilers. Severe myodegeneration, increased hypoxia, reduced blood flow, and increased collagen deposition are hallmark characteristics of WB that culminate in unsatisfactory fresh meat quality attributes, such as poor water-holding capacity, tenderness, and processing characteristics. Therefore, WB meat is often downgraded resulting in economic losses for the United States poultry industry. Although WB has been well characterized, its etiology remains undefined. As the scientific community continues to resolve mechanisms responsible for WB onset, understanding biochemical changes associated with WB may facilitate solutions to negate its poor meat quality attributes. Given changes in metabolism of living muscle can alter biochemical processes during the conversion of muscle to meat, this review aims to summarize and discuss the current knowledge of WB muscle and meat biochemistry. For example, it appears metabolic pathways that support combating stress are upregulated in WB muscle at the expense of glycolytic flux, which presumably contributes to the high ultimate pH of WB meat. Further, perturbed function of WB mitochondria, such as altered calcium handling, impacts aspects of postmortem metabolism and proteolysis. Collectively, metabolic dysfunction of WB muscle alters the biochemical processes that occur during the conversion of muscle to meat, and thus contributes to the poor WB meat quality.